AUTONOMY AT THE END OF LIFE IN THE FACE OF CONGOLESE SOCIO-CULTURAL BELIEFS, PRACTICES AND VALUES - MAKINDU, Darius (MEDECINE LEGALE DROIT MEDICAL, 2025)
This paper focuses on the autonomy of elderly patients at the end of life in the Congolese socio-cultural context. For a good understanding, we evoke the socio-cultural context of the philosophers E. Kant and J.S. Mill where the absolute individual freedom and the dignity of the human person constitute the base of the respect of autonomy. Questioning the respect of autonomy at the end of life in the Congolese context, the role of the caregiver and the family in the decision-making process concerning treatment choices and the patient’s will or preferences, and the patient’s right to information, it appears that the family is always and already involved in this process. Family reunion is a common practice at critical moments in life, such as the end of a person’s life. On this occasion, it is the joint decision that takes precedence over the will of the individual concerned. The Congolese socio-cultural organization supports the primacy of the community over the individual and the interdependence of human beings as described in the “Ubuntu” philosophy. Here, the family or community is the value of values. It is the guarantor of all values. We also present other values and conceptions (such as life after death) that do not allow for autonomy at the end of life in the perspective of euthanasia and assisted suicide.